2012
DOI: 10.1002/bab.1000
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the integral membrane proteins EGFR and FGFR3 in anti‐apoptotic Chinese hamster ovary cell lines

Abstract: Membrane proteins such as receptor tyrosine kinases (RTKs) have a vital role in many cellular functions, making them potential targets for therapeutic research. In this study, we investigated the coexpression of the anti-apoptosis gene Bcl-x(L) with model membrane proteins as a means of increasing membrane protein expression in mammalian cells. Chinese hamster ovary (CHO) cells expressing heterologous Bcl-x(L) and wild-type CHO cells were transfected with either epidermal growth factor receptor or fibroblast g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Membrane biogenesis is known to be enriched in murine cells, but these findings also suggest that this category of proteins may also be low in M-CHO cells 29 , 30 . Although M-CHO cells are widely used both for secreted and membrane protein expression, poor expression of membrane proteins has been previously reported 31 . In order to further examine the presence of key membrane and vesicle proteins in M-CHO cells, we applied three different enrichment methods to explore the M-CHO membranome.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane biogenesis is known to be enriched in murine cells, but these findings also suggest that this category of proteins may also be low in M-CHO cells 29 , 30 . Although M-CHO cells are widely used both for secreted and membrane protein expression, poor expression of membrane proteins has been previously reported 31 . In order to further examine the presence of key membrane and vesicle proteins in M-CHO cells, we applied three different enrichment methods to explore the M-CHO membranome.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative approaches have been suggested to overcome toxicity issues associated with MP overexpression. Ohsfeldt et al (2012) designed an anti-apoptosis strategy involving coexpression of Bcl-xL gene (encodes for an antiapoptotic protein) aiming to prevent cell death by bioreactor stresses, nutrient depletion, toxin accumulation, and stresses due to folding and processing requirements for complex proteins such as MP. The authors observed that cell death are diminished due to the co-expression of the anti-apoptotic gene and transient production of two different receptors were improved (Ohsfeldt et al 2012).…”
Section: Parametermentioning
confidence: 99%
“…Co-expression of the anti-apoptotic protein Bcl-x L in CHO cells improved the expression of epidermal growth factor receptor, fibroblast growth factor receptor 3 and receptor tyrosine kinases proteins [37]. Knock-out of the genes encoding the pro-apoptotic factors Bax and Bak in a CHO-K1 cell line improved cell viability, reduced levels of transfection-induced apoptosis and led to up to 4 fold higher antibody titers [38].…”
Section: Cell Proliferation and Survival Engineeringmentioning
confidence: 99%